2021
DOI: 10.1002/ajpa.24240
|View full text |Cite
|
Sign up to set email alerts
|

Shared paternal ancestry of Han, Tai‐Kadai‐speaking, and Austronesian‐speaking populations as revealed by the high resolution phylogeny of O1a‐M119 and distribution of its sub‐lineages within China

Abstract: Objectives: The aim of this research was to explore the origin, diversification, and demographic history of O1a-M119 over the past 10,000 years, as well as its role during the formation of East Asian and Southeast Asian populations, particularly the Han, Tai-Kadai-speaking, and Austronesian-speaking populations. Materials and Methods: Y-chromosome sequences (n = 141) of the O1a-M119 lineage, including 17 newly generated in this study, were used to reconstruct a revised phylogenetic tree with age estimates, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 74 publications
(162 reference statements)
2
30
0
Order By: Relevance
“…S4 and table S5 , Supplementary Material online). We note the limitation that all molecular dates have some level of uncertainty ( supplementary tables S3–S5 , Supplementary Material online), and not all known O1-M119 diversity is included here ( Sun et al 2021 ). Nevertheless, the striking radiations observed are characteristic of a diverse population of Mainland Asian origin moving into ISEA and expanding rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…S4 and table S5 , Supplementary Material online). We note the limitation that all molecular dates have some level of uncertainty ( supplementary tables S3–S5 , Supplementary Material online), and not all known O1-M119 diversity is included here ( Sun et al 2021 ). Nevertheless, the striking radiations observed are characteristic of a diverse population of Mainland Asian origin moving into ISEA and expanding rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…The overwhelming southward population dispersal from the central plain around the Yellow River Basin ( YRB ) of North-East Asia in the past two thousand years resulted in the formation of Han populations in southern China (Guang-Lin He et al, 2021; G. He et al, 2020; J. Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, it is also generally accepted that this process was accompanied by a large scale of integration with the southern aborigines (Guang-Lin He et al, 2021; G. He et al, 2020; J. Sun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Southern China was the originated center of many dominant uniparental lineages of southern Chinese indigenous populations and Southeast Asians ( Ke et al, 2001 ; Wen et al, 2004 ; He et al, 2020 ; Sun et al, 2021 ). Sun et al provided a higher-resolution phylogeny of O1a-M119 and found this founding lineage widely existed in modern Austronesian-, Tai–Kadai-speaking populations, and southern Han Chinese, suggesting that O1a-M119 lineage was the common lineage of these populations, and the diversified sub-lineages of O1a-M119 were their unique downstream paternal lineages ( Sun et al, 2021 ). Other population genetic studies of Southeast Asians also identified other paternal founding lineages, including O1b1a1a-M95 and O2-M122 ( Wen et al, 2004 ).…”
Section: Resultsmentioning
confidence: 99%